2022
DOI: 10.3390/met12071197
|View full text |Cite
|
Sign up to set email alerts
|

Abrasion Power of Ti and Ni Diamond-Coated Coatings Deposited by Cold Spray

Abstract: In this work, the cold spray technique was used to deposit nickel and titanium coated diamond powder on cast iron and aluminum substrates. To analyze the deposition mechanism, the diamond powders were observed before and after the process using a microscope and scanning electron microscope (SEM). The adhesion response of the Ni and Ti coatings was investigated during the study. Pin-on-disk tests were then performed to identify the abrasion mechanism of the coated samples and the wear resistance of the Si3N4 ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
(35 reference statements)
1
0
0
Order By: Relevance
“…According to Archard's wear law, there is an inverse relation between microhardness and wear volume in a tribological test. This relation is confirmed for coatings, abrasive coatings [32], and for HEA coatings. In Figure 8 it can be observed that, for the investigated HEA coatings, the wear behavior increases with the average microhardness, thanks to better microstructural characteristics.…”
Section: Resultssupporting
confidence: 62%
“…According to Archard's wear law, there is an inverse relation between microhardness and wear volume in a tribological test. This relation is confirmed for coatings, abrasive coatings [32], and for HEA coatings. In Figure 8 it can be observed that, for the investigated HEA coatings, the wear behavior increases with the average microhardness, thanks to better microstructural characteristics.…”
Section: Resultssupporting
confidence: 62%